Kinetic theory of the inner magnetospheric plasma - Khazanov, G. V. (Georgii Vladimirovich); SpringerLink (Online service). (New York Springer, 2010)
This book provides a broad introduction to the kinetic theory of space plasma physics with the major focus on the inner magnetospheric plasma. It is designed to provide a comprehensive description of the different kinds of transport equations for both plasma particles and waves with an emphasis on the applicability and limitations of each set of equations. The major topics are: Kinetic Theory of Superthermal Electrons, Kinetic Foundation of the Hydrodynamic Description of Space Plasmas (including wave-particle interaction processes), and Kinetic Theory of the Terrestrial Ring Current. Distinguishable features of this book are the analytical solutions of simplified transport equations. Approximate analytic solutions of transport phenomena are very useful because they help us gain physical insight into how the system responds to varying sources of mass, momentum and energy and also to various external boundary conditions. They also provide us a convenient method to test the validity of complicated numerical models, a task that is usually tedious and time consuming. This book will provide students and space researchers with an understanding of how to determine the best approach to any upper atmospheric or space physics problem.
Preface -- Introduction -- Kinetic Equations and Particle Collisions -- General Description of Wave Particle Interaction Phenomena -- Hydrodynamic Description of Space Plasma -- Analysis of Superthermal Electron Transport -- Analysis of Cold Plasma Transport -- Kinetic Theory of Superthermal Electron Transport -- Kinetic Superthermal Electron Instabilities in the Ionosphere -- Kinetic Theory of Ring Current and Electromagnetic Ion Cyclotron Waves: Fundamentals -- Kinetic Theory of Ring Current and Electromagnetic Ion Cyclotron Waves: Applications -- Concluding Remarks.
Electronic reproduction.
Keywords: Space plasmas; Magnetosphere; Electronic books